Professions and roles of Jewish personalities in the Umayyad state in Andalusia (138-422 AH / 755-1030 AD) (Hasday ibn Shabrout) as a model, a historical study (Journal of the College of Basic Education, 2022)
On the subject and study of Andalusia, it is considered one of the most important topics in the history of the Islamic` state, especially in the spread of Islamic civilization in all its aspects to the countries of Europe and the extent of peaceful coexistence between one society within the framework of the Islamic state and the teachings of the tolerant Islamic religion. In Andalusia (138-422 AH/ 755-1030AD)(Hasday bin Shabrout) as a historical study model) and through the title it is clear that the positions, leadership roles and professions were not monopolized, or the proximity of the rulers, princes and caliphs in Andalusia was to Muslims, but it was to the people of dhimma (Jews - and Christians) In particular, the Jews are a large part of those roles and positions, and they occupy the highest positions and ranks in the Islamic state in Andalusia. The research is divided into an introduction to the definition and naming of the country of Andalusia and four demands that include the conditions of the Jews before Islam, the Jews in the Holy Qur’an, the conditions of the Jews after the Islamic conquest of Andalusia, and the personality of (Hasday Ibn Shabrout and roles).